62.3k views
2 votes
Solve,3²*+¹=4(³*)+1=0​

1 Answer

1 vote

Answer:

3

2

x

x

3

1

28

(

3

x

3

1

)

+

1

=

0

Let

u

=

3

x

Now

3

u

2

28

(

u

3

)

+

1

=

0

3

u

2

28

u

3

+

1

=

0

9

u

2

28

u

+

3

=

0

Using the quadratic equation

u

1

,

2

=

b

±

b

2

4

a

c

2

a

you get

u

=

28

±

28

2

4

×

9

×

3

2

×

9

u

=

28

±

784

108

18

u

=

28

±

676

18

u

=

28

±

26

18

u

=

54

18

or

u

=

2

18

u

=

3

or

u

=

1

9

Put

3

x

back in for

u

to get

3

x

=

3

or

3

x

=

1

9

3

x

=

3

1

or

3

x

=

3

2

Therefore,

x

=

1

or

x

=

2

Step-by-step explanation:

User Sadek
by
4.9k points